People's perceptions and uses of invasive plant Psidium guajava in Vhembe Biosphere Reserve, Limpopo Province of South Africa. Issue 1 (31st December 2022) - Ruwanza, Sheunesu; Thondhlana, Gladman
ABSTRACT: Human perceptions and knowledge of invasive alien plant species are increasingly recognised as important in the management of biological invasions, but there is limited research focus on the social dimensions of plant invasion. Using household surveys, this study assessed the perceptions, knowledge, and uses of Psidium guajava Linn. to rural communities in Vhembe Biosphere Reserve, in the Limpopo Province of South Africa. Results showed that most respondents are aware of P. guajava and perceive it to be spreading in their locality but do not consider it an invasive alien plant species. Psidium guajava is perceived to have a dual purpose and most respondents are aware of its benefits including fruit consumption, medicinal purposes, shading and firewood provisioning and costs such as attraction of problematic animals, displacement of native plants, and reduction of grazing and agricultural space. The benefits associated with use of P. guajava are considered greater than the costs, therefore most participants do not implement any control measures. These results highlight the need to incorporate rural community perceptions, knowledge, and uses of P. guajava in developing effective management plans that avoid conflicts between stakeholders. To improve the efficacy of managing biological invasions more research is required to understand how communities relate to invasive alien plant species.